COMPARISON OF REDUNDANCY LEVELS USINGSTOCHASTIC ORDERINGS - Mohsin, Habeeb; Shaker, Shawki; Adnan, Alia’a (Iraqi Journal of Science, 2024)
In this research we concern with the comparison between the two ways ofproviding redundant units for a system:-1. Component redundancy.2. System redundancy.The comparison between these ways is carried out by comparing the randomvariable representing the lifetime of the system resulted from applying componentredundancy with the random variable representing the lifetime of that resulted fromapplying system redundancy using some types of stochastic orderings, namely:(1) usual stochastic ordering, (2) failure rate ordering, (3) likelihood ratio ordering,(4) reversed failure rate ordering and (5) mean residual life ordering.